TRAF6-Dependent Mitogen-Activated Protein Kinase Activation Differentially Regulates the Production of Interleukin-12 by Macrophages in Response to Toxoplasma gondii - Mason, Nicola J. (American Society for Microbiology, 2004)
The production of interleukin-12 (IL-12) is critical to the development of innate and adaptive immune responses required for the control of intracellular pathogens. Many microbial products signal through Toll-like receptors (TLR) and activate NF-κB family members that are required for the production of IL-12. Recent studies suggest that components of the TLR pathway are required for the production of IL-12 in response to the parasite Toxoplasma gondii; however, the production of IL-12 in response to this parasite is independent of NF-κB activation. The adaptor molecule TRAF6 is involved in TLR signaling pathways and associates with serine/threonine kinases involved in the activation of both NF-κB and mitogen-activated protein kinase (MAPK). To elucidate the intracellular signaling pathways involved in the production of IL-12 in response to soluble toxoplasma antigen (STAg), wild-type and TRAF6(−/−) mice were inoculated with STAg, and the production of IL-12(p40) was determined. TRAF6(−/−) mice failed to produce IL-12(p40) in response to STAg, and TRAF6(−/−) macrophages stimulated with STAg also failed to produce IL-12(p40). Studies using Western blot analysis of wild-type and TRAF6(−/−) macrophages revealed that stimulation with STAg resulted in the rapid TRAF6-dependent phosphorylation of p38 and extracellular signal-related kinase, which differentially regulated the production of IL-12(p40). The studies presented here demonstrate for the first time that the production of IL-12(p40) in response to toxoplasma is dependent upon TRAF6 and p38 MAPK.